Validação analítica de método em HPLC-PDA para avaliação do perfil de exposição a solventes orgânicos aromáticos em comunidade universitária - Honório, Tereza Cristina de Deus (2013)
Introduction: Aromatic organic solvents (AOS) are widely used in diverse industrial and laborer activities among others involving manipulating of products likes lacquers, inks and varnishes. Among the most commonly used AOS are toluene, xylene, styrene, ethylbenzene and phenol. Occupational exposure to these compounds can cause damage to the body, which leads to a concern about the health of the worker. Biological monitoring is an important tool used to evaluate exposition to chemical substances in the work environment, that consists of quantify the biomarkers of occupational exposure in biological samples. Brazilian values of AOS biomarkers and maximum allowable biological index (IBMP) are described in the NR7 of the Brazilian legislation (Ministério do Trabalho e Emprego, MTE). Objective: The aim of this work was to validate technical in HPLC-PDA for quantifying the exposure’s biomarkers and than evaluate the exposure’s profile to toluene, xylene, styrene, ethylbenzene and phenol in workers exposed in university community. Methods: To analyze the AOS biomarkers in urine samples by HPLC-PDA, method validation was done according to the preconized parameters by ANVISA described in RE 899/2003. Participate of the study 30 occupationally exposed volunteers that provided urine samples and asked a questionnaire survey to characterize the sampling. The sampling’s characterization was done by applying a survey to volunteers. Both descriptive and multivariate statitical analysis was performed to the analytical and surveying data. Results: The analytical method was to validate and appropriated for the purposes established. About 3,3 % of the volunteers presented levels of hipuric acid above of the allowed by the law. Besides, it was detected 3,4-methylhipuric acids in 13,3 % of volunteers in concentration below the maximum allowable limit. The main symptoms reported were headache, dyspnea, numbness and cough. Conclusion: The analytical method was within acceptable limits. It was observed that higher levels of hippuric acid in volunteers may be linked to a lack of protective equipment and collective environmental protection equipment, and high weekly workload. Additionally, methyl hippuric acid was found below IBMP. It was demonstrated a correlation between exposure to AOS biomarkers and symptoms reported by the volunteers.